2010
DOI: 10.1002/dc.21558
|View full text |Cite
|
Sign up to set email alerts
|

Solitary intrascrotal neurofibroma: A case diagnosed on aspiration cytology

Abstract: Solitary neurofibroma of the scrotum is exceedingly rare and very few cases of this unusual occurrance have been reported till date. None of the previously reported cases had a preoperative cytologic diagnosis. A young man presented with an eight-month history of right scrotal swelling. Fine-needle aspiration cytology showed a spindle cell tumor with fibrillary matrix and wavy slender nuclei. A cytologic diagnosis of benign nerve sheath tumor was rendered. The patient underwent surgical excision of the mass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Isolated intrascrotal neurofibroma unrelated to NF–I is very rare. According to the literature review, only 14 cases are reported 1 . Here we report a confirmed case of neurofibroma of vas deferens.…”
Section: Introductionmentioning
confidence: 74%
“…Isolated intrascrotal neurofibroma unrelated to NF–I is very rare. According to the literature review, only 14 cases are reported 1 . Here we report a confirmed case of neurofibroma of vas deferens.…”
Section: Introductionmentioning
confidence: 74%
“…[3] Neurofibroma of scrotum in the absence of NF I is extremely rare and to the best of our knowledge, about 10 cases [Table 1] have been reported in the English literature so far. [2] Solitary scrotal neurofibroma of the scrotum has been reported in a wide range of ages, mostly presenting with painless or painful swelling of the scrotal area. [410]…”
Section: Discussionmentioning
confidence: 99%
“…[1] Solitary scrotal neurofibromas unassociated with neurofibromatosis type I (NF I) are extremely rare and to the best of our knowledge, only 10 cases have been reported in the English literature. [2] Herein, we report a patient with scrotal mass who was diagnosed as scrotal neurofibroma after pathologic examination.…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibroma is a rare benign tumour of the scrotum, with less than 10 cases reported to date in humans (Issa et al 1993, Mishra et al 2002, Turkyilmaz et al 2004, Trovarelli et al 2006, Shibano et al 2010, Gupta et al 2011, Hosseini et al 2012. To the authors' knowledge, none have thus far been reported in animals.…”
Section: Introductionmentioning
confidence: 99%